ODP Leg 188, Hole 1165C - Well Logging Data - O'Brien, Philip E.; Cooper, Alan K.; Richter, Carl; Barr, Samantha R.; Bohaty, Steven M.; Claypool, George E.; Damuth, John E.; Erwin, Patrick S.; Florindo, Fabio; Forsberg, Carl Fredrik; Grützner, Jens; Handwerger, David A.; et al. (Zenodo, 2021)
Logging data are measurements of physical properties of the formation surrounding a borehole, acquired in situ after completion of coring (wireline logging) or during drilling (Logging-While-Drilling, LWD). The range of data (resistivity, gamma radiation, velocity, density, borehole images,…) in any hole depends on the scientific objectives and operational constraints. : ODP Leg 188: Prydz Bay-Cooperation Sea, Antarctica: Glacial History and Oceanography